Resident Doctors' Experiences in Breaking Bad News: The Level of Using Spikes Protocol and Related Factors - Esra Çınar Tanrıverdi; Yasemin Çayır; Banu Çiçek Dilfiruz (Journal of Medical Education and Family Medicine)
ABSTRACTObjective: This study aimed to determine assistant doctors' experiences of giving bad news, their use of the SPIKES protocol, and effective factors.Methods: The study was conducted at Atatürk University Faculty of Medicine between September-December 2017 with 232 assistant doctors. The participants' experiences of delivering bad news were assessed using a questionnaire based on the SPIKES protocol. The questionnaire, consisting of 20 questions on a five-point Likert scale, covered six key areas: environment, perception, invitation, information, affect, and plan-summary. Factors that could affect participants' methods of breaking bad news were questioned. Significance level was accepted as P<.05.Results: Of the participants, 57.3% (n=133 were male, 57.3% (n=133) were married, and 70.3% (n=163) were working in internal sciences. Mean age was 29±3.5 years, and mean total working time was 4.5±3.3 years. 64.7% (n=150) had no pre-graduation training in giving bad news, and 90.9% (n=211) had no post-graduation training. 38% felt competent, 35.8% found difficulty in giving bad news. 60.8% devoted enough time to interviews, 24.1% arranged quiet rooms, and 43.1% used warning sentences, and 75.9% empathized, 69% had quiet rooms during interviews. All participants allowed their emotions, and 84.9% made eye contact. Male participants introduced themselves more frequently than females before interviews (P<.05).Conclusion: To gain the skill of giving bad news of assistant doctors the training needs should be met and they should be supported. More training and experience in areas such as setting the environment, invitation and information are important, especially for the full implementation of the SPIKES protocol.